2020
DOI: 10.1103/physrevfluids.5.044001
|View full text |Cite
|
Sign up to set email alerts
|

Jet breakup in superfluid and normal liquid He4

Abstract: Past studies have shown that liquid jet breakup behavior can be classified into five regimes: Rayleigh, first wind, sinuous, second wind, and atomization. By experimentally examining the breakup of superfluid and normal liquid 4 He in an atmosphere of its own vapor, we investigate the evolution of the jet behavior over a large range of the traditional three-dimensional parameter space of the Ohnesorge number [Oh l ∼ O(10 −5-10 −2)], Reynolds number [Re l ∼ O(10 2-10 6)], and gas-liquid density ratio [ρ g /ρ l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…39 It has been pointed out that no obvious effects due to superfluidity have been observed on the breakup behavior of a liquid He jet. 14 Yet, Kolatzki et al 16 have found that He droplets undergo shape oscillations that persist for much longer times than in the case of viscous drops, a signature of the superfluid character of these droplets.…”
Section: He Nanoscopic Jetmentioning
confidence: 99%
See 3 more Smart Citations
“…39 It has been pointed out that no obvious effects due to superfluidity have been observed on the breakup behavior of a liquid He jet. 14 Yet, Kolatzki et al 16 have found that He droplets undergo shape oscillations that persist for much longer times than in the case of viscous drops, a signature of the superfluid character of these droplets.…”
Section: He Nanoscopic Jetmentioning
confidence: 99%
“…As with classical fluids, He jet breaking may lead not only to droplets but also to filaments, as observed in experiments. [14][15][16] We model here these filaments as cylinders of radius R 0 delimited by two hemispherical caps 19 and study, using the He-TDDFT approach, their contraction due to the effect of the surface tension for different values of the aspect ratio Γ = L/R 0 , 18 where L is the half-length of the filament from end-to-end. The configuration from which the real-time dynamics is initiated is a free-standing ideal filament (i.e.…”
Section: B Contraction and Fragmentation Of Free-standing Filamentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This unique fluid allows for a large variation of non-dimensional parameters related to the fluid viscosity and the velocity at which it exits the nozzle, which characterize its dynamical properties. 14 This understanding also has a primary application, namely to make available 4 He drops with the size and velocity required by the experiments, together with size and velocity distributions as narrow as possible. This has led to recent experimental studies on the disintegration of liquid 4 He jets.…”
Section: Introductionmentioning
confidence: 99%